Algorithms and parallel computing - Gebali, Fayez; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
'There is a software gap between the hardware potential and the performance that can be attained using today's software parallel program development tools. The tools need manual intervention by the programmer to parallelize the code. Programming a parallel computer requires closely studying the target algorithm or application, more so than in the traditional sequential programming we have all learned. The programmer must be aware of the communication and data dependencies of the algorithm or application. This book provides the techniques to explore the possible ways to program a parallel computer for a given application'--
'This book provides the techniques to explore the possible ways to program a parallel computer for a given application'--
Frontmatter -- Introduction -- Enhancing Uniprocessor Performance -- Parallel Computers -- Shared-Memory Multiprocessors -- Interconnection Networks -- Concurrency Platforms -- Ad Hoc Techniques for Parallel Algorithms -- Nonserialb6(BParallel Algorithms -- -Transform Analysis -- Dependence Graph Analysis -- Computational Geometry Analysis -- Case Study: One-Dimensional IIR Digital Filters -- Case Study: Two- and Three-Dimensional Digital Filters -- Case Study: Multirate Decimators and Interpolators -- Case Study: Pattern Matching -- Case Study: Motion Estimation for Video Compression -- Case Study: Multiplication over GF(2) -- Case Study: Polynomial Division over GF(2) -- The Fast Fourier Transform -- Solving Systems of Linear Equations -- Solving Partial Differential Equations Using Finite Difference Method -- References -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Parallel processing (Electronic computers); Computer algorithms; Computer science; Parallel processing (Electronic computers); Computer algorithms; COMPUTERS -- Networking -- General; Computer algorithms; Parallel processing (Electronic computers); Parallel processing (Electronic computers); Computer algorithms; Electronic books